Engineered Polysaccharides: α‐1, 3‐Glucan Acetates Showing Upper Critical Solution Temperature in Organic Solvents. Issue 16 (24th July 2019) - Heinze, Thomas; Pfeifer, Annett; Koschella, Andreas; Adelman, Douglas; Howe, Laurie; Behabtu, Natnael; Lenges, Christian
Abstract: Acetates of α‐1, 3‐glucan dissolved in N, N ‐dimethyl acetamide/LiCl are prepared by converting the polysaccharide with acetyl chloride, acetic acid anhydride/pyridine, or with acetic acid/ N, N ′‐carbonyl diimidazole. Values of the degree of substitution for the acetyl groups (DSAc ) of up to 2.6 are realized. NMR spectroscopic measurements reveal a preferred conversion of the primary hydroxyl group at position 6 followed by positions 2 and 4. Depending on the DSAc, the samples may be soluble in solvents of different polarity at room temperature or at elevated temperatures showing upper critical solution temperature at DS of about 2.5. This process is found to be reversible. Abstract : A biosynthetically produced α‐1, 3‐glucan is subjected to acetylation under homogeneous reaction conditions. A reactivity order O ‐6 > O ‐2 ≫ O ‐4 is found. The structure of the polymer in solution might prevent complete esterification. The acetates dissolve in solvents of different polarity and exhibit an upper critical solution temperature, that is, they dissolve at elevated temperatures while forming a gel upon cooling.